Molecular characterization of a novel strain of Bacillus halotolerans protecting wheat from sheath blight disease caused by Rhizoctonia solani Kühn - Feng, Zhibin; Xu, Mingzhi; Yang, Jin; Zhang, Renhong; Geng, Zigui; Mao, Tingting; Sheng, Yuting; Wang, Limin; Zhang, Juan; Zhang, Hongxia (Frontiers in Plant Science, 2022)
Rhizoctonia solani Kühn naturally infects and causes Sheath blight disease in cereal crops such as wheat, rice and maize, leading to severe reduction in grain yield and quality. In this work, a new bacterial strain Bacillus halotolerans LDFZ001 showing efficient antagonistic activity against the pathogenic strain Rhizoctonia solani Kühn sh-1 was isolated. Antagonistic, phylogenetic and whole genome sequencing analyses demonstrate that Bacillus halotolerans LDFZ001 strongly suppressed the growth of Rhizoctonia solani Kühn sh-1, showed a close evolutionary relationship with B. halotolerans F41-3, and possessed a 3,965,118 bp circular chromosome. Bioinformatic analysis demonstrated that the genome of Bacillus halotolerans LDFZ001 contained ten secondary metabolite biosynthetic gene clusters (BGCs) encoding five non-ribosomal peptide synthases, two polyketide synthase, two terpene synthases and one bacteriocin synthase, and a new kijanimicin biosynthetic gene cluster which might be responsible for the biosynthesis of novel compounds. Gene-editing experiments revealed that functional expression of phosphopantetheinyl transferase (SFP) and major facilitator superfamily (MFS) transporter genes in Bacillus halotolerans LDFZ001 was essential for its antifungal activity against R. solani Kühn sh-1. Moreover, the existence of two identical chitosanases may also make contribution to the antipathogen activity of Bacillus halotolerans LDFZ001. Our findings will provide fundamental information for the identification and isolation of new sheath blight resistant genes and bacterial strains which have a great potential to be used for the production of bacterial control agents. Importance A new Bacillus halotolerans strain Bacillus halotolerans LDFZ001 resistant to sheath blight in wheat is isolated. Bacillus halotolerans LDFZ001 harbors a new kijanimicin biosynthetic gene cluster, and the functional expression of SFP and MFS contribute to its antipathogen ability.